2008
DOI: 10.1097/pec.0b013e31816ffbe8
|View full text |Cite
|
Sign up to set email alerts
|

Noninvasive Respiratory Support

Abstract: Noninvasive ventilation (NIV) refers to the delivery of ventilatory support using techniques that do not require an endotracheal airway. Noninvasive ventilation is being used with increased frequency in a variety of clinical situations in the emergency department, intensive care unit, and prehospital environment. This article reviews the history of NIV, the rationale for its use, and the evidence of efficacy in both the adult and pediatric literature. This article also describes equipment and techniques curren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 62 publications
0
12
0
1
Order By: Relevance
“…Numerous experiences have been reported in studies showing the feasibility and lack of complications using CPAP to treat ACPE in out-of-hospital emergencies,11,174,175 with improvement in short-term outcomes 175…”
Section: Where To Apply Nivmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous experiences have been reported in studies showing the feasibility and lack of complications using CPAP to treat ACPE in out-of-hospital emergencies,11,174,175 with improvement in short-term outcomes 175…”
Section: Where To Apply Nivmentioning
confidence: 99%
“…A recent survey carried out in USA showed that the use of NIV to treat acute exacerbations of chronic obstructive pulmonary disease (COPD) increased more than 400% in one decade (from 1% in 1998 to 4.5% in 2008) and was associated with a 42% reduction in IMV 7. NIV is now a first-line therapy in emergency departments,8 regular hospital wards,9 palliative10 or pediatric11 care units, and even in out-of-hospital patients 12,13…”
Section: Introductionmentioning
confidence: 99%
“…NIV techniques have developed over the last 80 years and have been increasingly refined in the last 20 years since their use begun in obstructive sleep apnoea and related conditions [5]. The use of NIV in adult critical care patients has shown benefits when compared to intubation or venturi mask in terms of mortality, reduced length of stay, reduced ventilator-associated pneumonia and associated cost savings [6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…BiPAP provides respiratory support by unloading the diaphragm and accessory muscles, increasing tidal volume and minute ventilation, opening obstructed or collapsed alveoli, and decreasing the frequency of occlusive apnea and hypopnea [15,16]. Effective administration of BiPAP requires a well-fitted mask, optimal patient-ventilator synchrony (i.e., appropriate patient mental status and cooperation), and well-trained pediatric respiratory therapists to continuously monitor the circuit.…”
Section: Introductionmentioning
confidence: 99%
“…However, use of BiPAP as a beneficial treatment modality for acute severe asthma exacerbations in children is becoming more widely described and accepted in children of all weights [6][7][8][9][10][11][12][13][14][15][16][17][18][19]. The purpose of this study is to assess and report the safety of BiPAP use with traditional therapies for the treatment of acute severe asthma exacerbations in children who weigh 20 kg or less in the PED population.…”
Section: Introductionmentioning
confidence: 99%